(untitled) (Italian Journal of Public Health, 2011)
Background: Heart Rate Variability (HRV) analysis is easy to perform, has good reproducibility and provides prognostic information about Coronary Heart Disease. Objective: This work was devised to correlate exercise induced HRV with BMI and compare gender variability among healthy Indian children aged 13-20 years. Methods: The Heart Rate Variability of sixty-five students in the 13-20 years age group was assessed by time- domain methods during resting and after exercise. On the basis of BMI, the subjects were grouped into T1 group (BMI<18) and T2 group (≥18). The HRV of these groups were analyzed. In addition, based on gender, male students were divided on the basis of BMI as follows: M1 group <18 and M2 group ≥ 18. Likewise females were grouped into F1 and F2 groups. The HRV of 3 male groups and 3 female groups were also separately analysed. A paired t- test was used for the dependent variables and an unpaired t-test was carried out for normally distributed variables using Statistical Package for Social Sciences (SPSS) 11.0 for windows. Results: Females showed higher HRV than males during resting condition. But immediately after exercise, the HRV increased in all groups and there was no difference in HRV based on gender and BMI. When recorded 5 minutes after exercise, the HRV decreased further regardless of gender and BMI. However, the HRV taken 30 minutes after exercise behaved more like the resting condition. The HRV recorded 30 minutes after exercise increased from the “5 minutes after exerciseú value but still remained lower in all groups regardless of gender and BMI. Conclusions: The results demonstrate that, in healthy adolescents, the parasympathetic activity is higher in females than in males during the rest period. Exercise induced sympathetic activity lasts longer in females with higher BMI and lower age, resulting in decreased HRV.